Sharenting perspectives of Gen Z parents on posting their preschool-aged children on social media - Latayan, Jaila Deanna B.; Regis, Renae Louise J.
Sharenting is a widespread phenomenon that proliferated in social media sites, such as Facebook and Instagram. Despite Gen Z individuals being considered as “digital natives”, there is a lack of study concerning the parents of the generations, specifically in the local context. The researchers aim to inquire into the perspectives of Gen Z parents on the practice of sharenting through exploring their deciding factors, identifying their perceived benefits and risks, and describing the sharented contents. Through purposive sampling, a total of 20 participants consisting of 10 mothers and 10 fathers. They answered a pre-interview questionnaire and went through an interview. The data gathered were transcribed and analyzed thematically. Results show that Gen Z parents perceive a few types of content as sensitive because of the risks associated with this. They then employ privacy-protective behaviors in order to mitigate this risk. Finally, parents would post sharented contents in order to realize its benefits. In conclusion, Gen Z parents generally view sharenting in a positive light. For them, the benefits outweigh the risks. Some of the parents are not too concerned about the risks with the confidence they will not be subjected to such. Despite this, Filipino Gen Z parents employ strategies in order to somehow mitigate risks to protect their children. All these considered, the researchers recommended additional criteria for respondents for further analysis of sharenting practices, as well as the dissemination of information on the practice of sharenting through social media outlets.